Complete Protection Strategy for Loss of Excitation in Large-Scale Synchronous Condensers Applied to UHVDC Transmission - Zhilin Guo; Liangliang Hao; Jinghan He; Zhengguang Chen; Xingguo Wang (CSEE Journal of Power and Energy Systems)
Large-scale synchronous condenser (LSC) has a broad application prospect in China's ultra-high voltage direct current (UHVDC) to provide dynamic reactive power. Loss of excitation (LOE) is an important grid-related fault of LSC, resulting in uncontrolled reactive power consumption. However, due to the un obvious fault feature and UHVDC's diverse reactive power demands, LSC's LOE protection faces challenges in criterion and action mode configurations. Thus, this paper proposes a complete LOE protection strategy for the LSC used in UHVDC, including effective criterion and proper action mode. First, the defect of existing reverse reactive power-based protection is presented through an in-depth analysis of the LOE LSC's reactive power behavior. Then, excitation current difference between the measured value and equivalent actual value is identified as the new fault feature. Compared with existing reverse reactive power features which also appear in healthy LSC's leading phase conditions, this current difference feature only appears in the LO E process and thus is more typical. Since actual excitation current is unmeasurable in practice, an estimation model is built and validated by experiment and simulation. Moreover, the novel LOE protection strategy including current-based criterion and improved action mode is proposed. Through comparative simulation studies in PSCADIEMTDC, the novel protection exhibits superior performances compared to existing protection in LOE detection and commutation failure immunity improvement, as well as overvoltage suppression.